2022
DOI: 10.1002/pon.5937
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden for caregivers of adolescents and young adults with cancer

Abstract: Objective: Adolescent and young adult (AYA) cancer survivors are vulnerable to cancer-related financial burden, which is likely shared by their caregivers. This study aims to enhance an existing conceptual model of financial burden by conducting concept elicitation interviews with caregivers to generate knowledge that can be translated to inform instrumental and psychosocial support in cancer care. Methods: Qualitative concept elicitation interviews were conducted with 24 caregivers of AYA cancer survivors (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…As such, findings suggest parents need support navigating relationship difficulties and seeking social support. Results also suggest some parents experience financial difficulties, which is particularly important given previous research suggesting financial difficulties correlate with poor mental health during cancer treatment 36 and that parents would like support locating financial resources 37 Future adaptations of EJDeR will include information and signposting for difficulties concerning relationships, finance, and employment.…”
Section: Discussionmentioning
confidence: 87%
“…As such, findings suggest parents need support navigating relationship difficulties and seeking social support. Results also suggest some parents experience financial difficulties, which is particularly important given previous research suggesting financial difficulties correlate with poor mental health during cancer treatment 36 and that parents would like support locating financial resources 37 Future adaptations of EJDeR will include information and signposting for difficulties concerning relationships, finance, and employment.…”
Section: Discussionmentioning
confidence: 87%
“…Another study of partners of patients with cancer in South Korea reported an association of caregivers’ lost savings and income with a negative impact on HRQoL . In a recent study of caregivers of adolescent and young adult cancer survivors, researchers observed high financial burden for 25% of caregivers, often secondary to employment disruptions and costs of care . In addition, a 2021 study of survivors of multiple cancer types reported associations between pain and negative survivor financial and employment outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…38 In a recent study of caregivers of adolescent and young adult cancer survivors, researchers observed high financial burden for 25% of caregivers, often secondary to employment disruptions and costs of care. 39 In addition, a 2021 study of survivors of multiple cancer types reported associations between pain and negative survivor financial and employment outcomes. 40 Our results extend beyond those of prior studies to further confirm and identify mechanistic factors in the association between FT and specific domains of partner HRQoL.…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%
“…A study from India has reported that nonmedical expenses of childhood cancer treatment account for 22% to 46% of the monthly income of families 12 . Out-of-pocket spending remains a significant challenge for caregivers of children with cancer in low-income settings 13 . Pandemics and other crises can exacerbate the financial burden on families of children with cancer, amplifying their impact 14 …”
Section: Discussionmentioning
confidence: 99%